Resilience to crisis through social protection: Can we build the case? - Thomas Roca; Hélène Ferrer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper investigates the linkage between social protection and economic resilience. Does social protection have an impact on income? What role do social protection policies play in strengthening a society's capacity to overcome economic hardships? The recent crisis has brought these questions to the forefront of the discussions among development institutions. Our panel analysis suggests a positive answer to the first question and provides empirical evidence showing that social protection may be an effective means of reducing poverty and accelerating economic development. The answer to the second question remains more elusive as data availability issues hamper fine-tuning our investigation.
Keywords: O11; O4; H50; I31; 330; social protection; public spending; growth; financial crisis; resilience